The Life Cycle of Tussock Moth (Lymantria curvifera) and the Phytochemical Analysis of the Host Plant, Talisay Tree (Terminalia catappa) - Mavingeri, Lorna; Simatele, Abel; Esplana, Ferdinand A. (11th International Scholars Conference, 2018)
Talisay trees were infested by numerous black unknown larvae that left it entirely leafless at the Adventist University of the Philippines campus. No record of infestation among Talisay trees has been established that prompted the researchers to study the life cycle of the larvae and the host plant. This study examined the relationship between the Tussock moth (Lymantria curvifera) specie and its host plant, Talisay tree (Terminalia catappa). More so, the study aimed to identify the phytochemicals present in the Talisay tree. Results showed that the tree is rich in glycosides and tannins that aid in the moth’s life cycle development. Other phytochemicals present in the tree include flavonoids, saponins and sterols. The entire life cycle of the Tussock moth takes two months to complete from oviposition to adult. After oviposition, it takes an average of five days for the egg to hatch to larvae. The larvae starts with a smooth body, as it develops, the body develops hairy tussocks. The larval stage progresses to the pupal stage after an average of five days and an average of seventeen days to become a fully developed adult moth.